(untitled) (International Journal of Built Environment and Sustainability, 2016)
In contrast to the one whole homogenous configuration provided by developers that has often proved ineffective overtime, transformed public housing units are widespread in developing cities. Though transformation is a natural phenomenon of inhabitation, its various levels and degree can have implicit values. In recent times in Nigeria, heterogeneous spatial patterns of transformed houses in public housing estates has given empirical evidence of essentially inevitable reflection of culture sensitivity as hypothesized by previous studies. That hints that the mainstream sustainable values were probably ignored during design process. This study attempted to connect that possible missing link. To achieve that aim, it developed two objectives. First, is to identify core values behind space layouts in the mainstream. Then, to examine how they exist in the transformed layout as reflected at communal origins. It investigated on 42 transformed units in selected urban Public housings neighborhoods via a stratified conditional sampling conducted in five states of Nigeria. Qualitative methods were adopted for data analysis. After identifying the core ethnic groups in the region, their social indicators with regards to space use were determined through ethnographic principles. These indicators were then operationally defined, and used as a tool to examine users’ motivations in the transformation process in urban context. Spatial pattern analysis, by using gamma delineation, revealed the social content in the transformations after comparing initial design and the transformed spatial configurations. The outcome signified the mainstream cultural values in the transformation process hence in Public housing design. The convergence of mainstream values into urban transformed layouts suggested that they cannot be ignored during design process. The outcome of this research might be useful in designing sustainable public housings in culture sensitive environments, better still a guide to Architects and developers in this regard.